Parents' calcium knowledge is associated with parental practices to promote calcium intake among parents of early adolescent children - Gunther, C.; Rose, A.; Bruhn, C.; Cluskey, M.; Reicks, M.; Richards, R.; Wong, S.; Boushey, Carol; Misner, S.; Olson, B. (2015)
The study reported here aimed to identify the relationship of parents' calcium knowledge with dietrelated parental practices and determinants of calcium knowledge. A cross-sectional survey was conducted measuring parental practices, calcium knowledge, and demographics. A convenience sample of 599 racially/ethnically diverse parents of children 10-13y completed questionnaires. Higher education and having a daughter were associated with higher calcium knowledge; being Asian or Hispanic and born outside the U.S. were associated with lower calcium knowledge. Parents with greater calcium knowledge were more likely to engage in healthy parenting practices. These factors may be important considerations for Extension educators in nutrition education.